Tumour-infiltrating lymphocytes and prognosis in different subtypes of breast cancer: a pooled analysis of 3771 patients treated with neoadjuvant therapy. Issue 1 (January 2018) - Denkert, Carsten; von Minckwitz, Gunter; Darb-Esfahani, Silvia; Lederer, Bianca; Heppner, Barbara I; Weber, Karsten E; Budczies, Jan; Huober, Jens; Klauschen, Frederick; Furlanetto, Jenny; Schmitt, Wolfgang D; Blohmer, Jens-Uwe; et al.
Summary: Background: Tumour-infiltrating lymphocytes (TILs) are predictive for response to neoadjuvant chemotherapy in triple-negative breast cancer (TNBC) and HER2-positive breast cancer, but their role in luminal breast cancer and the effect of TILs on prognosis in all subtypes is less clear. Here, we assessed the relevance of TILs for chemotherapy response and prognosis in patients with TNBC, HER2-positive breast cancer, and luminal–HER2-negative breast cancer. Methods: Patients with primary breast cancer who were treated with neoadjuvant combination chemotherapy were included from six randomised trials done by the German Breast Cancer Group. Pretherapeutic core biopsies from 3771 patients included in these studies were assessed for the number of stromal TILs by standardised methods according to the guidelines of the International TIL working group. TILs were analysed both as a continuous parameter and in three predefined groups of low (0–10% immune cells in stromal tissue within the tumour), intermediate (11–59%), and high TILs (≥60%). We used these data in univariable and multivariable statistical models to assess the association between TIL concentration and pathological complete response in all patients, and between the amount of TILs and disease-free survival and overall survival in 2560 patients from five of the six clinical trial cohorts. Findings: In the luminal–HER2-negative breast cancer subtype, a pathological complete response (pCR) was achieved in 45 (6%) of 759 patients with low TILs, 48 (11%) of 435 with intermediate TILs, and 49 (28%) of 172 with high TILs. In the HER2-positive subtype, pCR was observed in 194 (32%) of 605 patients with low TILs, 198 (39%) of 512 with intermediate TILs, and 127 (48%) of 262 with high TILs. Finally, in the TNBC subtype, pCR was achieved in 80 (31%) of 260 patients with low TILs, 117 (31%) of 373 with intermediate TILs, and 136 (50%) of 273 with high TILs (p<0·0001 for each subtype, χ 2 test for trend). In the univariable analysis, a 10% increase in TILs was associated with longer disease-free survival in TNBC (hazard ratio [HR] 0·93 [95% CI 0·87–0·98], p=0·011) and HER2-positive breast cancer (0·94 [0·89–0·99], p=0·017), but not in luminal–HER2-negative tumours (1·02 [0·96–1·09], p=0·46). The increase in TILs was also associated with longer overall survival in TNBC (0·92 [0·86–0·99], p=0·032), but had no association in HER2-positive breast cancer (0·94 [0·86–1·02], p=0·11), and was associated with shorter overall survival in luminal–HER2-negative tumours (1·10 [1·02–1·19], p=0·011). Interpretation: Increased TIL concentration predicted response to neoadjuvant chemotherapy in all molecular subtypes assessed, and was also associated with a survival benefit in HER2-positive breast cancer and TNBC. By contrast, increased TILs were an adverse prognostic factor for survival in luminal–HER2-negative breast cancer, suggesting a different biology of the immunological infiltrate in this subtype. Our data support the hypothesis that breast cancer is immunogenic and might be targetable by immune-modulating therapies. In light of the results in luminal breast cancer, further research investigating the interaction of the immune system with different types of endocrine therapy is warranted. Funding: Deutsche Krebshilfe and European Commission.